Metaversos e jogos digitais multijogador: aspectos históricos e metodológicos de uma abordagem do ciberespaço - Pontuschka, Maigon Nacib (2012)
This dissertation studies metaverses and multiplayer digital games, a theme that is deeply associated with an increasingly participatory, collaborative and fundamentally massive digital world. It identifies the elements and core characteristics that allow the delimitation of metaverses and multiplayer digital games as a field of research, its applications and the aspects associated with pragmatic development techniques. It organizes and analyzes a thematic overview whose structure stems from the recent history of digital games, from statistical research and, particularly, from the developments that resulted in the multiplayer approaches. It proposes a classification based on constituent ontological pragmatical properties. It applies the resulting classification into organizing an approach that shows the relationship between academic research, research developed by independent game producers, as well as companies producing game engines and metaverses. With the resulting classification of the metaverses and digital games, it presents a description and an analysis of model examples, emphasizing their evolutionary history characteristics, their technical development scope and their practical applications. The dissertation brings together a body of information that shows an overview of current research and leads the way to a possible methodology for evaluating the use and development of metaverses and digital games. It culminates in the evaluation of the concept of academic game, with a view to drawing up specifications for the development of an academic metaverse entitled Pirarucu-Gente